PARTICIPATION OF VOTERS WITH DISABILITIES IN ELECTION IN INDONESIA: A COMPARATIVE STUDY OF KPU STRATEGIES IN SEMARANG AND MALANG - Nurul Alam, Sutan Agung; Cahyo Seftyono; Moh. Nizar (Jurnal Sosiologi Dialektika Sosial, 2025)
Voters with disabilities still face a number of structural and cultural barriers in exercising their right to vote. Therefore, the approach taken by the General Elections Commission (KPU) in ensuring inclusive participation is crucial to analyses. This study aims to explore differences in the approaches used, the factors that influence them, and provide suggestions for implementing more disability-friendly elections in various locations. This paper will compare the KPU strategies in Semarang City and Malang City in encouraging disabled voter participation in the 2024 General Election using a comparative literature study method analyzed using Peter Schroder's political strategy theory. Data were collected through literature studies and in-depth interviews with several informants. The study's findings indicate that the Malang City Election Commission (KPU) was more innovative, involving democracy volunteers, providing specialized services at polling stations (TPS), and building close collaborations with various institutions. In contrast, the Semarang City Election Commission (KPU) took a more cautious approach, focusing primarily on digital service innovation. However, other strategies, such as voter education and outreach, remained passive and limited in scope, as they did not reach all groups of people with disabilities, particularly those not integrated into formal communities.